Molecular detection of sars-cov-2 (covid-19) in stray cats in kota bharu, kelantan - Jeremy Tan Jianhao (2022)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement for the course DVT55204 – Research Project. In late 2019, Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) emerged in the city of Wuhan, China and quickly spread all over the world causing the latest pandemic. Due to the close association between humans and animals including companion animals, livestock and wildlife species, the potential transmission of SARS-CoV-2 from humans to animals, which is known as “reverse zoonosis” as well as the potential role infected animals might have in the spread of the disease has become a concern. This study was done to detect the presence of SARS-CoV-2 infection in stray cats in Kota Bharu, Kelantan. Oropharyngeal swabs were taken from 15 stray cats from Kota Bharu, Kelantan where the RNA was extracted, amplified with reverse transcription-polymerase chain reaction (RT-PCR) and run through agarose gel electrophoresis. The results revealed that all cats tested negative for SARS-CoV-2 infection thus, concluding that there is a 0% occurrence of SARS-CoV-2 infection in stray cats from Kota Bharu, Kelantan. Keywords: SARS-CoV-2, COVID-19, RT-PCR, stray cats, reverse zoonosis, occurrence